Chemistry in confined spaces: reactivity of the Zn-MOF-74 channels. Issue 34 (9th August 2016) - Zuluaga, S.; Fuentes-Fernandez, E. M. A.; Tan, K.; Arter, C. A.; Li, J.; Chabal, Y. J.; Thonhauser, T.
Abstract : Once the water dissociation reaction takes place at the metal centers, the addition of 40 Torr of CO at 200 °C starts the production of formic acid via OH + H + CO → HCO2 H. Abstract : Using infrared spectroscopy combined with ab initio methods we study reactions of H2 O and CO inside the confined spaces of Zn-MOF-74 channels. Our results show that, once the water dissociation reaction H2 O → OH + H takes place at the metal centers, the addition of 40 Torr of CO at 200 °C starts the production of formic acid via OH + H + CO → HCO2 H. Our detailed analysis shows that the overall reaction H2 O + CO → HCO2 H takes place in the confinement of MOF-74 without an external catalyst, unlike the same reaction on flat surfaces. This discovery has several important consequences: it opens the door to a new set of catalytic reactions inside the channels of the MOF-74 system, it suggests that a recovery of the MOF's adsorption capacity is possible after it has been exposed to water (which in turn stabilizes its crystal structure), and it produces the important industrial feedstock formic acid.